Enhancing Quality and Safety of Garlic Pulp through Ohmic Heating: A Comprehensive Study on Physicochemical, Microbiological, and Bioactive Content - P, Poojitha; S, Priyanka; Koshy, Nirmal Abraham; P, Gurumoothy; Athmaselvi, K A (International Journal of Membrane Science and Technology, 2023)
This research paper investigates the application of ohmic heating as an innovative method to improve the quality and safety of garlic pulp. Garlic is a widely consumed vegetable renowned for its unique flavor and potent bioactive compounds, but traditional processing methods often degrade its bioactive constituents and pose microbial safety concerns. In this study, the researchers explore the potential of ohmic heating to address these issues. The study begins by examining the physicochemical properties of garlic pulp subjected to ohmic heating, including changes in pH, color, texture, and moisture content. The results reveal that ohmic heating effectively preserves overall quality attributes, with notable improvements in color and texture compared to conventional processing methods. Additionally, the impact of ohmic heating on the bioactive content of garlic pulp is investigated. High-performance liquid chromatography (HPLC) analysis reveals that ohmic heating leads to superior retention of key bioactive compound diallyl disulfide. By preserving physicochemical properties, enhancing microbial safety, and retaining bioactive content, ohmic heating offers a novel approach to elevate the nutritional and safety standards of garlic-based products. These findings have significant implications for the food industry, providing valuable insights into the potential benefits of adopting ohmic heating technology.